Dual defect system of tellurium antisites and silver interstitials in off-stoichiometric Bi2(Te, Se)3+y causing enhanced thermoelectric performance. Issue 2 (17th December 2018) - Kim, Cham; Lopez, David Humberto; Kim, Dong Hwan; Kim, Hoyoung
Abstract : Thermoelectric performance was significantly enhanced with off-stoichiometric Bi2 (Te, Se)3+ y having the dual defect system of Te antisites and Ag interstitials. Abstract : Enhancement in the thermoelectric performance of n-type Bi2 (Te, Se)3 was accomplished by forming a dual defect system composed of Te- and Ag-related defects. Te-rich Bi2 (Te, Se)3+ y, which has antisite defects generated by an excess of Te, was prepared via a conventional melting process. We devised a one-pot process in which Ag nanoparticles were deposited onto the Te-rich Bi2 (Te, Se)3+ y as soon as they were chemically synthesized, followed by a sintering compaction; thus, we aimed at selective insertion of Ag atoms into the interstitial sites of the Te-rich Bi2 (Te, Se)3+ y . The resulting Ag interstitials interact with the Te antisite defects to vary the thermoelectric transport properties of the product. We endeavored to balance the concentration of the defects to maximize the phonon glass electron crystal (PGEC) characteristic of the product, resulting in excellent thermoelectric performance in low temperature regions – we achieved the highest ZT average values, below 150 °C ( ZT ave = 1.18 (25–100 °C) and 1.15 (25–150 °C)), ever reported for n-type Bi2 (Te, Se)3 materials.